HUBUNGAN KECEMASAN IBU YANG MELAHIRKAN BAYI BERAT LAHIR RENDAH DENGAN PENGELUARAN KOLOSTRUM - Sudarti, Achmad Surjono, Indira Laksmi (Universitas Respati Yogyakarta, 2010)
This research generally has aimed to find out correlation of low weight birth mother and secretion period of colostrums in prenatal room, installation of maternal prenatal of Dr. Sardjito Hospital Yogyakarta. Specifically, this research has aimed to find out correlation of low weight birth mother and ccilostrums secretion period, and to find out correlation of anxiety rate of low weight birth mother with colostrums secretion period.The. determining of anxiety, mother education, age of pregnancy and observation place is not influence to mother anxiety. It's caused of existing of extension and knowledge of birth processing and breastfeeding. While, paritas, childbirth manner and mother age is influence to anxiety. It's caused minimal experience about childbirth.Spontaneous group childbirth has high total score of anxiety and colostrums secretion. While, mother age has positive correlation with anxiety score. The older of mother age cause control of anxiety is increase.Linier regression analysis show anxiety score influence to colostrums secretion period. Anxiety total score has positive correlation to colostrums secretion period. The higher of anxiety rate of mother childbirth, colostrums secretion period is increase. When, the other factors are constant, low weight birth mother still has colostrums secretion period as 42,75 hours. When anxiety score is increase 1 unit, anxiety score will support of colostrums secretion period as long as 1.78 hours.Keywords: low weight birth mother, anxiety, secretion of colostrums